Father-child religious transmission from Adolescence to Young Adult: the moderating effect of father-child relationship quality - Nicholson, Bornell (Kansas State University, 2020)
Fathers play a significant role in the continuation of adolescent to young adults’ religiosity. Fathers transmit their religiosity through communicating beliefs and modeling practices (e.g., praying, attending church, engaging in other religious rituals). As adolescent transition to young adulthood, they seek increasing independence and seek a faith that is their own. Parents have a significant influence during this time. A small body of research demonstrates that fathers play a unique role in the development of offspring religiosity. What is less known is under what conditions father religiosity predicts young adult religiosity? Utilizing two waves from the Add Health data I test the moderating influence of father-child relationship quality on the link between fathers’ religiosity and young adults’ religiosity among a sample of 242 father-child dyads. Results indicate that Wave I father religiosity predicted Wave III young adult religiosity. However, father-child relationship quality, was not found to significantly moderate the association between father and young adults’ religiosity. Implications for parents, clergy, and therapists/counselors are discussed. Future research is needed to examine other potential moderators of the father-child religious transmission.
Keywords: Father-child relationship quality; Religiosity; Fathers; Young adults; Adolescents